Stabilization of microtubule dynamics by estramustine by binding to a novel site in tubulin: A possible mechanistic basis for its antitumor action - Panda, Dulal (The National Academy of Sciences of the USA, 1997)
The cellular targets for estramustine, an antitumor drug used in the treatment of hormone-refractory prostate cancer, are believed to be the spindle microtubules responsible for chromosome separation at mitosis. Estramustine only weakly inhibits polymerization of purified tubulin into microtubules by binding to tubulin (K(d), ≈30 μM) at a site distinct from the colchicine or the vinblastine binding sites. However, by video microscopy, we find that estramustine strongly stabilizes growing and shortening dynamics at plus ends of bovine brain microtubules devoid of microtubule-associated proteins at concentrations substantially below those required to inhibit polymerization of the microtubules. Estramustine strongly reduced the rate and extent both of shortening and growing, increased the percentage of time the microtubules spent in an attenuated state, neither growing nor shortening detectably, and reduced the overall dynamicity of the microtubules. Significantly, the combined suppressive effects of vinblastine and estramustine on the rate and extent of shortening and dynamicity were additive. Thus, like the antimitotic mechanisms of action of the antitumor drugs vinblastine and taxol, the antimitotic mechanism of action of estramustine may be due to kinetic stabilization of spindle microtubule dynamics. The results may explain the mechanistic basis for the benefit derived from combined use of estramustine with vinblastine or taxol, two other drugs that target microtubules, in the treatment of hormone-refractory prostate cancer.